Characterisation of the surface geometry of 3D printed scaffolds for cell infiltration and surgical suturing - Ruiz-Cantu, Laura; Gleadall, Andrew; Faris, Callum; Segal, Joel; Shakesheff, Kevin M.; Yang, Jing (IOP Publishing, 2016)
3D printing is of great interest for tissue engineering scaffolds due to the ability to form complex geometries and control internal structures, including porosity and pore size. The porous structure of scaffolds plays an important role in cell ingrowth and nutrition infusion. Although the internal porosity and pore size of 3D printed scaffolds have been frequently studied, the surface porosity and pore size, which are critical for cell infiltration and mass transport, have not been investigated. The surface geometry can differ considerably from the internal scaffold structure depending on the 3D printing process. It is vital to be able to control the surface geometry of scaffolds as well as the internal structure to fabricate optimal architectures. This work presents a method to control the surface porosity and pore size of 3D printed scaffolds. Six scaffold designs have been printed with surface porosities ranging from 3% - 21%. We have characterised the overall scaffold porosity and surface porosity using optical microscopy and microCT. It has been found that surface porosity has a significant impact on cell infiltration and proliferation. In addition, the porosity of the surface has been found to have an effect on mechanical properties and on the forces required to penetrate the scaffold with a surgical suturing needle. To the authors’ knowledge, this study is the first to investigate the surface geometry of extrusion-based 3D printed scaffolds and demonstrates the importance of surface geometry in cell infiltration and clinical manipulation